Transaneurysmal Suturing of Pseudoaneurysm Neck: Novel and Not a Pseudo-Technique for Treatment of Complicated Femoral Pseudoaneurysm - Niraj Kumar; Chandan Kumar Pal; Somsharan Shankerappa Betgeri; Amar Mukund (Indian Journal of Radiology and Imaging)
Introduction Femoral pseudoaneurysm is one of the common complications following femoral artery catheterization. It poses a significant morbidity and a nonsurgical technique with the utmost low complication risk is warranted. Various methods have been used to treat these pseudoaneurysms including manual compression, ultrasound-guided compression, and percutaneous injection of thrombin or glue. Various novel methods are also being used to treat the pseudoaneurysms, including angioseal closure device, vascular plugs, etc. Cirrhosis poses a separate challenge with deranged coagulation and hyperfibrinolysis, making traditional methods, which are dependent on patients' coagulation cascade, less effective.